Digital adaptation in education: A case study and intervention proposal - Ferreira, C.; Costa, P. (Digital technologies and transformation in business, industry and organizations, 2022)
Education is one of the most important pillars of our society, thus there is a constant need of adapting to new contexts. The COVID-19 pandemic impacted schools and demanded change in technological literacy. This case study, conducted in a European public school, aims at understanding the context and developing an intervention under the assessment of the pandemic’s impact on such organizations. Hence, a literature review was performed, comprising a framing of the current conditions and relevant constructs to cope with change. Examples of the last are reflexivity, psychological safety and adaptivity. This review led to the diagnosis and the intervention proposal development following Porras’ [23] and Kurt Lewin’s (1947) change models. The diagnosis encompassed the conduction of interviews and focus groups. Hence, several intervention proposals framed by the job demands and resources model by Bakker et al. (Annu Rev Organ Psych Organ Behav 1:389–411, 2014) were developed. All the proposals are presented in this chapter, as well as their desired effects. From the data gathering process and its following analysis, the needs of the school arose, and topics such as exhaustion, the perception of low digital skills, the inability of establishing barriers, lack of digital resources and technologies’ integration, as well as a weak internal communication were mentioned.